Pengaruh Myofascial Release Technique Terhadap Penurunan Nyeri Fascitiis Plantaris Pada Sales Promotion Girl Di Ramayana Bekasi - Berbudi B L, Abdurahman; Ali, Mohammad; Ritonga, Azis; Muazarrah, Dhyah (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Introduction: the use of high heels for a long time can cause plantar fasciitis (PF). PF caused by inflammation or degeneration of plantar fascia tissue. Inflammation of plantar fascia occurs due to repetitive microtrauma and produces plantar fasciitis pain. One of physiotherapy interventions who can be used to treat PF is myofascial release technique or MFR. Research Purpose: The aim of this study was to determine effect of MFR for plantar fasciitis pain in high heel user. Methodology: the research used pre-experimental method, using one-group design pretest-posttest and the place in Ramayana Bekasi Proyek. The sample calculation based on lameshow formula obtained 18 respondents selected accrording to inclusion criteria. The measurement pain that use visual analogue scale to got the beginning and end of the data after given intervention of as 3 times a week for 3 weeks. Data were analyzed using univariate and bivariate test. Results: the result showed value of plantar fasciitis pain has decreased. The pain variables tested using Paired T-test, the mean value before intervention 32,67+14,24 and after intervention 20,39+12,33 with P value=0,0000 (P<0,05). Conclusion: there is an effect of myofascial release technique to decrease the fasciitis plantaris pain on sales promotion girl at Ramayana Bekasi Proyek in 2018.